STUDI WACANA KRITIS, PENGAJARAN BAHASA INDONESIA, DAN PERSPEKTIF EMANSIPASI - Anang Santoso (Fakultas Sastra Universitas Negeri Malang, 2015)
The characteristics of language use during this global era include: the instability of language, the prominence of language hybrid, discourse commodification and tecnologized discourse. Language has shown its role as the determinant factor for hegemony in which the Indonesian language teachers should consider. The teaching of Indonesian language should be developed based on critical discourse analysis. Consequently, the learners of Indonesian language might have awareness on language sensitivity on the basis of emancipation perspectives